La concepción de la violencia de género desde la perspectiva de los agresores en la ciudad de Macas durante los meses octubre 2015- febrero 2016, una aproximación desde las producciones narrativas - Flores Carvajal, Daniela Mishell (2016)
Our task as researchers of gender violence from the perspective of the aggressor is presented in this work by a tour that begins in a conceptual framework in which we laid the literary foundations of what the theory is about as gender violence , masculinity, patriarchy and an approach to possible solutions to violence. Second enunciate the methodology chosen to travel on this inquiry, it's where we refer to the narrative productions as a method of starting to approach the objectives. On the other hand the narrative productions are presented as a new research methodology that provides focus on particular stories but with great ability to explain phenomena such as gender violence results. Finally, we present the results obtained by a description consisting of narrative productions themselves, these are a talkative textualization on the accounts of the participants. We also do an analysis of results based on the interweaving of narrative productions with the conceptual framework, thus trying to describe certain dynamics that occur within gender violence by way of exposure not judging, because this methodology away from the positivist way to explain the phenomena. Ultimately we make our conclusions, where we emphasize on relevant points found throughout research, we focus on producing new ideas that circulate around the subject.